2003
DOI: 10.1042/bj20021696
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the lipocalin 24p3 as an apoptotic mechanism for MK886

Abstract: MK886, a strong proapoptotic agent, is an inhibitor of 5-lipoxygenase (LOX) through binding to the 5-LOX-activating protein (FLAP). Although MK886-induced apoptosis is through a FLAP-independent pathway, the precise mechanisms are not understood. In the present study, a possible role of 24p3, a lipocalin, in MK886-induced apoptosis was investigated. Exposure of murine prolymphoid progenitor cells (FL5.12) to 20 microM MK886 for 16 h dramatically increased 24p3 mRNA and protein expression. Induction could also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 41 publications
5
37
0
Order By: Relevance
“…6C). Bcl-2 family proteins have been previously implicated in the effects of lcn2 on the cell death and survival (28,29,31). In particular, up-regulation of proapoptotic Bim expression was essential for the apoptosis-inducing effects of lcn2 (29).…”
Section: Expression and Regulation Of Lcn2 Lcn2 Receptor (Lcn2/24p3rmentioning
confidence: 99%
“…6C). Bcl-2 family proteins have been previously implicated in the effects of lcn2 on the cell death and survival (28,29,31). In particular, up-regulation of proapoptotic Bim expression was essential for the apoptosis-inducing effects of lcn2 (29).…”
Section: Expression and Regulation Of Lcn2 Lcn2 Receptor (Lcn2/24p3rmentioning
confidence: 99%
“…These results indicate that the cell death-sensitizing activity of lcn2 in astrocytes is related to the iron transport and metabolism: apo-lcn2 may promote cell death by depleting intracellular iron, whereas holo-lcn2 containing the siderophore-iron complex may not. Bcl-2 family proteins have been previously implicated in the effects of lcn2 on cell death and survival (Yousefi and Simon, 2002;Tong et al, 2003;Devireddy et al, 2005). In particular, the upregulation of proapoptotic Bim expression was essential for the apoptosisinducing effects of lcn2 (Devireddy et al, 2005).…”
Section: Role Of Iron and Bim In The Cell Death-sensitizing Effects Omentioning
confidence: 99%
“…lcn2 is also known as 24p3 and neutrophil gelatinase-associated lipocalin (NGAL) (Borregaard and Cowland, 2006). In vitro studies have shown that lcn2 is important for both cellular apoptosis and survival (Devireddy et al, 2001(Devireddy et al, , 2005Yousefi and Simon, 2002;Tong et al, 2003Tong et al, , 2005Nelson et al, 2008). It also plays an important role in the induction of cellular differentiation in kidney during embryogenesis (Yang et al, 2002) and protects the kidney from ischemic injury (Mishra et al, 2004;Mori et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Lipocalins are part of a large family of proteins involved in the regulation of diverse cellular processes, partially with diverse outcomes (12). Lcn-2 is highly expressed during acute microbial infection as well as tissue involution, and has been shown recently to induce apoptosis of hematopoietic cells (13)(14)(15)(16)(17). However, work on Lcn-2 also suggested a role as mediator of cell growth and viability (18).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Lcn-2 in nonheart tissues was described by several authors with emphasis on epithelial and hematopoietic cell lines (human lung adenocarcinoma A549 cells, human breast cancer MCF7 cells (13), hematopoietic FL5.12 (14) and 32D (33) cells, etc. ), murine and human tissues (epithelium of lung (34), bowel (35), uterus (28), mammary epithelial cells (36), tubular epithelium of the kidney (37), adenocarcinoma of the breast, ovary and pancreas (38), leukocytes (39), etc.)…”
Section: Lcn-2 In Ischemia and Reperfusionmentioning
confidence: 99%